Pencegahan dan Penanggulangan Penyebaran COVID 19 pada Anak-Anak dengan Cara 4M - Puspita Ayu Marhaeni; Beti Prihandini; Sulastri Sulastri; Ni Nyoman Yeni; Ria Setia Sari (Syntax Idea, 2021)
The purpose of this community service is so that parents and children can understand the prevention and control of the spread of COVID-19 in children while utilizing 4M movements (washing hands, wearing masks, maintaining distance, avoiding crowds in the Indonesian language). The method used is health education and the practice of six steps to washing your hands. The results of this activity showed that children could understand and be interested in participating in health education on "prevention and control of the spread of COVID-19 to children by using 4M movements", and children and families are willing to implement protocols in their lives. The conclusion is that by implementing the 4M protocol in the family environment, we hope it can reduce the spread of COVID-19 in Indonesia